141k views
0 votes
If f(x) = log (x/4) and g(x) = 2 log x, find (g – f) (x).

User Original
by
5.0k points

2 Answers

0 votes

Explanation:

To find (g – f)(x), we can subtract f(x) from g(x):

(g – f)(x) = g(x) – f(x)

= 2 log x – log (x/4)

Using the logarithm identity log a - log b = log (a/b), we can rewrite the expression as:

(g – f)(x) = log x^2 - log (x/4)

= log (x^2/(x/4))

= log (4x)

Therefore, (g – f)(x) = log (4x).

User Ali Shekari
by
4.8k points
4 votes

Answer:

To find (g – f)(x), we need to subtract f(x) from g(x). We can do this by substituting the expressions for f(x) and g(x) into the difference:(g – f)(x) = g(x) – f(x)

= (2 log x) – (log (x/4))We can simplify this expression by using the fact that log a - log b = log (a/b). Applying this fact, we get:(g – f)(x) = (2 log x) – (log (x/4))

= log ((x^2) / (x/4))

= log (4x)Therefore, (g – f)(x) = log (4x).

Explanation:

User GodEater
by
5.4k points